Commodity Markets, Long-Run Predictability, and Intertemporal Pricing - Fernandez-Perez, Adrian; Fuertes, Ana-Maria; Miffre, Joelle (Review of Finance, 2017)
Abstract This article shows that commodity portfolios that capture the backwardation and contango phases exhibit in-sample and out-of-sample predictive power for the first two moments of the distribution of long-horizon aggregate equity market returns, and for the business cycle. It also demonstrates that a pricing model based on the corresponding backwardation and contango risk factors explains relatively well a wide cross-section of equity portfolios. The cross-sectional “hedging” risk prices are economically consistent with the direction of long-horizon predictability. Backwardation and contango thus act as plausible investment opportunity state variables in the context of Merton’s (1973) intertemporal capital asset pricing model.